(untitled) (Journal of Dhaka National Medical College & Hospital, 2021)
Background: Pregnancy has a profound impact on the thyroid gland & its function. Objective: To correlate TSH, FT4 & FT3 levels with gestational age to observe their relationship. Method: This cross sectional study was conducted in the Department of Physiology, Sir Salimullah Medical College, Dhaka from July 2016 to June 2017. Total 90 apparently healthy pregnant women of different trimesters, age ranged from 20 to 35 years were selected as study group (Group I). Again according to gestational age, study group was subdivided into 1st trimester of gestation (Group la, n=30), 2nd trimester of gestation (Group Ib, n=30) and 3rd trimester of gestation (Group Ic, n=30) respectively for comparison. For correlation, serum TSH, FT4 and FT3 levels were measured. The statistical analysis was done by Unpaired t test and Pearson’s correlation coefficient test. Results: In this study, mean serum TSH level was positively correlated with gestational age and both mean serum FT4 & FT3 levels were negatively correlated with gestational age and these relationships were statistically highly significant. Conclusion: There is a negative association of thyroid hormone (FT4 & FT3) levels with gestational age. J. Dhaka National Med. Coll. Hos. 2021; 27 (02): 07-10